2013
DOI: 10.1155/2013/603940
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silica‐Coated Magnetic Nanoparticles and Application in the Detection of Pathogenic Viruses

Abstract: Magnetic Fe3O4nanoparticles were prepared by coprecipitation and then coated with silica. These Fe3O4/SiO2nanoparticles consisted of a 10–15 nm magnetic core and a silica shell of 2–5 nm thickness. The superparamagnetic property of the Fe3O4/SiO2particles with the magnetization of 42.5 emu/g was confirmed by vibrating sample magnetometer (VSM). We further optimized buffers with these Fe3O4/SiO2nanoparticles to isolate genomic DNA of hepatitis virus type B (HBV) and of Epstein-Barr virus (EBV) for detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Quy et al (2013) have shown that the purification efficiency of DNA of both EBV and HBV using synthesized silica-coated Fe 3 O 4 MNPs was superior to that obtained with commercialized silica-coated Fe 3 O 4 magnetic microparticles. Quy et al (2013) reported also on time saving in detection of EBV and HBV, namely the time required for DNA purification using silica-coated Fe 3 O 4 nanoparticles was significantly reduced as the particles were attracted to magnets more quickly (15À20 seconds) than the commercialized silica-coated Fe 3 O 4 microparticles (about 2À3 minutes). These results were attributed to the fact that silica-coated Fe 3 O 4 nanoparticles have a larger total surface area compared to that of the commercialized silica-coated Fe 3 O 4 microparticles.…”
Section: Detection Of Pathogenic Virusesmentioning
confidence: 93%
See 4 more Smart Citations
“…Quy et al (2013) have shown that the purification efficiency of DNA of both EBV and HBV using synthesized silica-coated Fe 3 O 4 MNPs was superior to that obtained with commercialized silica-coated Fe 3 O 4 magnetic microparticles. Quy et al (2013) reported also on time saving in detection of EBV and HBV, namely the time required for DNA purification using silica-coated Fe 3 O 4 nanoparticles was significantly reduced as the particles were attracted to magnets more quickly (15À20 seconds) than the commercialized silica-coated Fe 3 O 4 microparticles (about 2À3 minutes). These results were attributed to the fact that silica-coated Fe 3 O 4 nanoparticles have a larger total surface area compared to that of the commercialized silica-coated Fe 3 O 4 microparticles.…”
Section: Detection Of Pathogenic Virusesmentioning
confidence: 93%
“…Several methods can be listed as precipitation: coprecipitation, microemulsion/inverse microemulsion, polyol, etc. Coprecipitation is a convenient way to synthesize Fe 3 O 4 nanoparticles (Lu et al, 2007;Quy et al, 2013;Dung et al, 2016;Khalil, 2015;Mascolo et al, 2013). The mixture of two chloride salts of FeCl 2 and FeCl 3 with 1:2 molar ratios of Fe 21 /Fe 31 was vigorously stirred and kept at 70 C before NH 4 OH was added resulting in the black color precipitation.…”
Section: Coprecipitationmentioning
confidence: 99%
See 3 more Smart Citations